Clinical evaluation of Kati basti and Shaman chikitsa in the Management of Lumbo-sciatic syndrome (Gridhrasi) (International Journal of Food and Nutritional Sciences, 2021)
Gridhrasi or Lumbo-sciatic syndrome (LSS) is well described in Ayurveda as Vata Nanatmaja disorder. Presently it is a very common problem comes for treatment in a routine clinic of a physician or Orthopedic surgeon. Young persons especially prone because of fast riding vehicles, uneven roads, long and faulty sitting as well as due to wrong weight lifting activities during gym exercises. The most common cause is inter-vertebral disc bulge, prolapse or herniation in order of severity, usually at L4-L5 and L5-S1 level and nerve compression. The patient of Gridhrasi has typically presented with pain radiating from low back to hip, to back of thigh, leg and ankle with tingling and numbness. Patient is unable to move for a long distance and his drive typically resembles to gait of a vulture. Contemporary medical treatments provide only a limited relief to the patients and many patients are either bed bound or lives with pain and discomfort in everyday life. Acharya Sushruta describes its treatment in Bhagna chapter and advises for use of Acchana (Traction-counter traction) and Sneha Basti (Oil pooling/ enema) to treat these disorders along with (Shamana chikitsa) subsidizing drugs. This clinical trial brings an objective assessment of the clinical improvement in LSS with Panchakarma therapy (Kati basti) and oral medication.